Enhanced Nucleate Pool Boiling by Coupling the Pinning Act and Cluster Bubble Nucleation of Micro-nano Composited Surfaces. (August 2020) - Liu, Bin; Yu, Lingmin; Zhang, Yonghai; Marco, Paolo Di; Wei, Jinjia
Research highlights: A new way was proposed to improve the boiling performance in the low surface tension liquid. The pinning act of bubbles and the cluster bubble nucleation were coupled. The boiling performance of the micro-nano composited surfaces are significantly improved. A unique bubble behavior named "microbubble explosive emission" was observed. The mechanism of bubble behavior was analyzed by a modified force-energy balance model. Abstract: A new idea by coupling the pinning act of the micro-pin-fins and the cluster bubble nucleation of nonuniform nanowalls, was proposed to improve the boiling performance on micro-nano composited surface in the low surface tension liquid. To realize this idea, the uniform/nonuniform nanowalls were composited on the smooth surface and micro-pin-finned surfaces. The pool boiling performance of a smooth surface, the uniform/nonuniform nanowall surfaces, micro-pin-finned surface, and micro-nano composited surfaces with uniform/nonuniform nanowalls were tested and compared with each other. Both the heat transfer coefficient (HTC) and critical heat flux (CHF) of the micro-nano composited surface with nonuniform nanowalls (named PFNW2) are significantly increased compared to the micro-pin-finned surface. In addition, small bubble departure diameters, high bubble departure frequency and velocity were also found on PFNW2. A unique bubble behavior, named microbubble explosive emission, was observed, which provides a strong evidence for the effectiveness of the method to enhance boiling heat transfer by coupling the pinning act of the micro-pin-fins and the cluster bubble nucleation. It is suggested that high liquid subcooling and modulated nanostructures for bubble departure promotion are both indispensable for further enhancement of HTC and CHF in low surface tension liquid. Graphical Abstract: Image, graphical abstract